GE_GERICHTE A/2043/2024 vom 23. Juni 2025 - GE Cour de justice (2025)
IMPÔT À LA SOURCE; DÉDUCTION SOCIALE(DOUBLE IMP.);PROCÉDURE DE TAXATION;RÉTROACTIVITÉ;LÉGALITÉ;ÉGALITÉ DE TRAITEMENT | LIFD.113.al1; LPFisc.16.al1; LIFD.85; LIFD.35.al2; LISP.3; LIPP.65; RISP.1.al3; LIFD.137.al1; LPFisc.38E.al1; LIFD.99A; LISP.15